The effects of mitochondrial DNA deletion and copy number variations on different exercise intensities in highly trained swimmers - Baykara, O.; Sahin, S. K.; Akbas, F.; Guven, M.; Onaran, I. (Cellular and Molecular Biology, 2016)
It has been suggested that heavy exercise might increase oxidative stress, causing mitochondrial DNA (mtDNA) mutations as well as DNA mutations and changes in the mtDNA copy number in cells. mtDNA4977 deletion is one of the most common deletions seen on mitochondria. We hypothesize association between exercise induced oxidative stress and mtDNA damage in peripheral blood lymphocytes (PBLs) of highly trained swimmers. Therefore we studied the mtDNA4977 deletion level, mtDNA copy number and their relationship with cellular ATP and oxidative stress status in PBLs of swimmers. 8 highly trained and 8 normal trained swimmers and 8 non-athlete subjects were included in the study. The mtDNA4977 deletion and amount of mtDNA were measured using RT-PCR method whereas dichlorohydrofluoroscein (DCF) assay method was used to assess cellular oxidative stress and ATP levels were measured using bioluminescence method. Even though an increase in mtDNA4977 deletion was found in all study groups, the difference was not statistically significant (p=0.98). The mtDNA copy numbers were found to be surprisingly high in highly trained swimmers compared to normal trained swimmers and non-athlete subjects by 4.03 fold (p= 0.0002) and 5.58 fold (p=0.0003), respectively. No significant differences were found between groups by means of intracellular ATP levels (p=0.406) and oxidative stress (p=0.430). No correlation was found between mtDNA copy number and intracellular ATP content of the PBLs (p=0.703). Our results suggest that heavy training does not have a specific effect on mtDNA4977 deletion but it may be affecting mitochondrial copy numbers which may act as a compensatory mechanism related to ATP levels in blood.